STRATEGI ADAPTASI EKONOMI NELAYAN BUGIS BATULAWANG, KEMUJAN, KARIMUNJAWA - Dhanang Respati Puguh; Rabith Jihan Amaruli; Mahendra P. Utama (Jurnal Sejarah Citra Lekha, 2016)
This paper discusses about economics adaptation strategies among Bugis’s fishermen in Batulawang, Kemujan, Karimunjawa. This region status has been changed since 1980s as a Marine Nature Reserve, and later became a National Park in the 1990s, it has led to significant changes socially and economically. A zonning enforcement conducted by the Karimunjawa National Park has been affected on gaining access of economic and livelihoods, it is forced people to adapt. There are several forms of economic adaptation strategies are executed, the faithful in fishing activity by modifying fishing gear and run the new economic activities related to the potential marine tourism in the region.